Biodegradasi Senyawa Toksik Naftalena Pencemar Lingkungan Menggunakan Isolat Fungi Indigen Provinsi Riau - Riryn Novianty (Jurnal Ipteks Terapan, 2019)
Napthalene is two ring aromatic of a group Polycylic Aromatic Hydrocarbons (PAHs) that is one priority pollutans established in nature which can cause carcinogenic. The aim of this study  is determine the effectiveness of three isolates of indigenous fungi from Riau Province to degrade naphthalene. The growth and the ability of isolates to degrade naphthalene were examined into liquid MM (Minimal Medium) containing 0.2 mM naphthalene for 16 days incubation.The potential of fungi isolates during the degradation process was influenced by several parameters, including biomass, pH and the percentage of degradation which was measured at 0, 4, 8, 12 and 16 days of incubation. The results showed that the three isolates could use the naphthalene substrate as an energy source. The three isolates can degraded naphthalene each 51.28% oleh Aspergillus sp. LBKURCC151, 55.13% oleh Aspergillus sp. LBKURCC152 dan 48.72% oleh Penicillium sp. LBKURCC153. LBKURCC152. In conclusion, Aspergillus sp. LBKURCC152 is the best isolate for naphthalene degradation in this research